Ultrasound-guided versus surgical transversus abdominis plane block in obese patients following cesarean section: a prospective randomised study - Urfalıoğlu,Aykut (2017)
Abstract Background and objectives Ultrasound-guided transversus abdominis plane block demonstrated efficacy in providing post-operative analgesia by prolonging the time to first analgesic requirement and reducing the total analgesic consumption. The surgical transversus abdominis plane block, a novel technique, can be performed safely in obese patients in whom muscle layers cannot be sufficiently exposed. Here, we compared applicability, efficacy and complications of surgical transversus abdominis plane and ultrasound-guided transversus abdominis plane blocks in obese pregnant women following cesarean section under general anesthesia. Methods Seventy-five pregnant women with pre- and post-pregnancy body mass index > 30 were randomized and allocated into two groups: Ultrasound-guided transversus abdominis plane block (UT group; n = 38) and surgical TAP block (ST group; n = 37). Visual analogue scale scores at post-operative 0, 2, 6, 12 and 24 hours (h), time to first analgesic requirement, total analgesic consumption amount in 24 h, post-operative side effects, complications and patient satisfaction were recorded. Results and conclusions Age, American Society of Anesthesiologist score, operative duration, body mass index, mean time to first analgesic requirement and total analgesic consumption in 24 h were similar between groups, while significant differences in pre- and post-pregnancy body mass index were observed between groups. Block procedure durations were 7 and 10 minutes in ST and UT groups, respectively. No significant differences in visual analogue scale scores were observed between the groups at all times; itching and nausea was observed in one (UT group) and four (UT and ST groups) patients, respectively. Surgical transversus abdominis plane block was safe in obese pregnant patients and provided similar post-operative analgesia to ultrasound-guided transversus abdominis plane block.